جرائم جلسات المحاكم: دراسة مقارنة - مطر، منتظر فيصل كاظم (جامعة بابل - كلية القانون, 2021)
يقصد بجرائم جلسات المحاكم هو كل فعل أو أمتناع عن فعل يشكل جريمة ترتكب من قبل أشخاص سواء كانوا أطراف في الدعوى الجزائية كالمشتكي أو المتهم أو وكلائهم من المحامين أو غيرهم من الحاضرين في جلسة المحكمة أو من قبل جهات كأن ترتكب من قبل هيئة المحكمة كالقاضي أو المدعي أو أحد موظفي الجلسة سواء كانت هذه الجريمة تشكل مخالفة أو جنحة أو جناية من شأنها عرقلة سير المحاكمة ومن ثم إعاقة عمل القضاء في الوصول إلى العدالة أو أن تقلل من هيبة المحكمة. أعطى التشريع العراقي للمحاكم بشأن جرائم جلسات المحاكم الحق في تحريك الدعاوى الجزائية فيها وأجراء التحقيق والمحاكمة وكذلك الحكم فيها ولكن ضمن حدود معينة، كما منح المحكمة سلطة التصدي للجرائم التي ترتكب أثناء انعقاد جلستها استثناء على مبدأ الفصل بين سلطتي الاتهام وسلطة الحكم، وذلك لأن المحكمة التي تقع في جلستها تكون هي الأقدر من غيرها على أثبات هذه الجريمة والفصل فيها، أضافة إلى ذلك أن المشرع العراقي قد وسع من سلطة المحاكم الجزائية وذلك كلا حسب نوع الجريمة والمحكمة. هذا وقد أعطى المشرع العراقي لجرائم جلسات المحاكم قواعد إجرائية خاصة تتمثل بقواعد الاختصاص الوظيفي والنوعي ومن حيث طبيعة الأشخاص وقواعد تحريك الدعوى والتحقيق والمحاكمة والطعن في الأحكام وقواعد الشكوى من القضاة وردهم. وكان منهج بحث هذه الدراسة تحليليا وتطبيقيا في قانون العقوبات العراقي رقم (١١١) لسنة ١٩٦٩ المعدل وقانون أصول المحاكمات الجزائية العراقي رقم (٢٣) لسنة ١٩٧١ المعدل وبقية القوانين الإجرائية العراقية الأخرى مع المقارنة مع نصوص التشريع الإجرائي الجنائي والمدني المصري والتطرق إلى بعض نصوص الدستور والقانون الجزائي الإيراني.
Courts sessions crimes are meant as every act or omission that constitutes a crime committed by persons, whether they are parties to the criminal case, such as the complainant, the accused, or their attorneys from the attorneys or others present in the court session or by entities such as if it is committed by the court, such as the judge or the plaintiff. Or one of the court employees, whether this crime constitutes a violation, misdemeanor, or a felony that would obstruct the progress of the trial and thus hinder the work of the judiciary in reaching justice or reduce the prestige of the court. Iraqi legislation has given criminal courts with regard to courts sessions crimes to initiate criminal cases, investigate and conduct the trial, as well as adjudicate them, but within certain limits, and it also gives these courts the authority to address crimes committed during their session, as an exception to the principle of separation Between the powers of accusation and the investigation, because the court in whose session the crime takes place is the most capable of proving this crime and adjudicating it, In addition the Iraqi legislator has expanded the authority Criminal courts, each according to the type of crime and the court. The Iraqi Legislature has given the crimes of court sessions its own procedural rules, which are the rules of professional and gender competence and in terms of persons, the rules of case movement, investigation, trial, appeals against judgments, and rules for complaints by judges and their response. The study of this research was an analytical study of Iraqi legislation, including the Penal Code No. (111) of 1969 amended, the Code of Criminal Procedure No. (23) of 1971 amended, and the rest of the other procedural laws with comparison with the texts of Egyptian criminal and civil legislation and touching on some provisions of the constitution and the Iranian penal code.
Keywords: جلسات المحاكم -- جرائم المحاكم -- العراق